Perancangan Board Game Sebagai Media Pengenalan Rempah-rempah Khas Indonesia Pada Anak Usia 9-12 Tahun - Viola Intan Prayogo; Arie Setiawan; Birmanti Setia Utami (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2025)
Indonesia is an agrarian country with abundant natural resources, one of which is spices. However, the wide variety of spices in Indonesia makes it difficult for younger generations to recognize and distinguish them. This lack of understanding is also influenced by the increasing number of instant products available. This study aims to develop an educational board game that introduces spices to children aged 9-12 years. The method used in this research is descriptive qualitative method through questionnaires, interviews, and data collections from journals, articles, and online sources. The design process consisted of conceptualization, design, and product development stages, followed by testing with experts ang the target audience. The results show that The Spice Lab board game can serve as an effective and enjoyable learning medium for children.